62 Which staff groups should provide endovascular thrombectomy in stroke? survey of professional attitudes amongst relevant clinicians. (June 2018) - Sharma, Harish; Radhakrishnan, Ashwin; Aziz, Amir; Sandhu, Kulwinder; Lake, Alison; Rogers, Sarah; Millward, Victoria; Trevelyan, Jasper
Abstract : Introduction: Stroke is the leading cause of neurological disability in the UK. The mainstay of treatment involves antiplatelets with or without thrombolysis, which only 12% of stroke emergencies in the UK are eligible to receive. Endovascular thrombectomy offers a novel treatment to enable revascularisation and limit stroke morbidity and mortality. A National Institute for Health and Care Excellence report confirms thrombectomy is safe and effective, and is associated with improved outcomes compared to both thrombolysis and medical therapy alone. While it is estimated that up to 9000 patients per year may be eligible for thrombectomy, its adoption in the UK has been slow. NHS England has announced that it will commission a 24/7 interventional stroke service. A significant obstacle to this goal is the increase in interventional operators required. Centres in Europe have demonstrated success in stroke thrombectomy by interventional cardiologists who have led and developed the service. There is growing interest in whether interventional cardiologists and the primary percutaneous intervention network can safely deliver this service in the UK. Methods: A questionnaire was developed to help service planning and to gather the views of West Midlands stroke physicians, interventional cardiologists and interventional radiologists. Clinicians were asked which professionals should perform thrombectomy, the minimum number of cases to be performed annually to maintain competence, whether on-site neurosurgical cover is required and whether they would be willing to partake in an oncall rota for this service. Results: 121 clinicians from 9 West Midlands trusts responded to our survey. Interventional radiologists were deemed the most suitable clinicians to carry out stroke thrombectomy (29.7% rising to 32.2% with appropriate training). Interventional cardiologists were voted second most suitable (14.4% rising to 22.3% with appropriate training). Thrombectomy by any professional with appropriate training was the least popular option. 95% of respondents agreed that a minimum number of annual cases should be performed to maintain competence, although the exact number varied significantly. 59% of clinicans felt that stroke thrombectomy could be performed without on-site neurosurgical cover. 72.5% of clinicians agreed to participate in an out of hours rota if stroke thrombectomy services were provided on a 24/7 basis. Conclusions: Stroke thrombectomy significantly improves outcomes following acute ischaemic strokes. Recommendations from our work are to: Restrict service development to centres with established interventional neuroradiology services and a co-located hyperacute stroke service. A phased approach to other centres for the development of interventional neuroradiology services. Consideration should be given to the potential for interventional cardiologists to perform this procedure if properly trained.